Estimating Malaysia's output gap: Have we closed the gap? - Nur Ain Shahrier, *; Chuah, Lay Lian (World Scientific Publishing Company, 2017)
The concepts of potential output and output gap are central to the policymakers’ analytical work in providing guidance to policy decisions. This paper presents three different estimation approaches for the Malaysian economy, namely, the univariate, multivariate and structural models. While the multivariate and structural models are mainly underpinned by theory and captured the concept of potential output better, most policymakers still maintain a suite of models to preserve diversity. Diversity provides a greater scope for cross-checking the robustness of results. The paper attempts to contribute by first, providing a critical assessment of the different models in estimating potential output and the output gap, and, second, the usefulness of each models in terms of assessing the drivers of future potential output, predicting price trends and identifying sources of inflation in the economy.